From hierarchies to networks: Possibilities and pitfalls for educational reform of the middle tier. Issue 5 (18th June 2019) - Chapman, Christopher
Abstract : Purpose: Historically, the school effectiveness and improvement movement has focussed its attention on "within school" factors associated with effectiveness and improvement and on the individual school as the primary unit of analysis for improvement and scrutiny purposes. More recently, research has focussed on school-to-school collaboration and engagement with a broader range of services and providers has highlighted the need for more adaptive and nuanced forms of collaboration and partnership. The purpose of this paper is to explore this complex landscape from the perspective of educational reform of the middle tier in Scotland. Design/methodology/approach: This paper draws on perspectives associated with socio-cultural theory, its application to public service settings and insights gained from research and evaluation outcomes over a five-year period. Findings: This paper focusses on the establishment of Regional Improvement Collaboratives in Scotland; an example of an attempt to generate system-wide change and a shift from the hierarchical cultures characterised by bureaucratic organisations to more egalitarian cultures characterised by mutualistic, laterally networked organisations. It highlights the importance of structure and cultural change, identity and agency, leadership capacity, outward perspectives, primacy of learning and teaching and variations and complexities in creating a more networked and collaborative education system. It offers cautions concerning potential unintended consequences in the quest to develop a "self-improving" or "learning system". Practical implications: This paper highlights the importance of maintaining and building social cohesion between different stakeholders within educational systems in order to support the implementation of educational reform. Originality/value: This is the first documentation and reflective analysis for an ambitious reform agenda for the middle tier in Scotland. Its value lies in the lessons and considerations it offers to other systems embarking on reforms that endeavour to build more cohesive and agile education systems, without opening them up to neo-liberal approaches to education.